Primary Omental Hydatid Cyst:- Report of Two Cases (Journal of Paediatric Surgeons of Bangladesh, 2016)
We are reporting two cases of primary omental hydatid cyst in children of 12 yr & 5yr of age respectively. Both cases were diagnosed on ultrasound & managed successfully by open surgical excision of the cyst. In our patients cyst were unilocular & in one of the patients it contained large numbers of daughter cysts (approx.150). We failed to find in literature a giant primary omental hydatid cyst with so many daughter scolexs of varying sizes.J. Paediatr. Surg. Bangladesh 5(2): 68-72, 2014 (July)